Virtual Load Theory: A General Approach for Mitigating Mutual Coupling in Antenna Arrays - Majid Manteghi (IEEE Access)
This paper introduces a generalized Virtual Load Theory (VLT) for mitigating mutual coupling in antenna arrays through digital signal preprocessing. The method employs Coupling Compensation Matrices (CCMs) derived from generalized Thévenin-Helmholtz equivalent circuits, formulated using impedance and scattering matrices. A key finding reveals that the scattering matrix-based CCM does not always align with the impedance matrix-based solution; this discrepancy is analyzed and resolved to ensure theoretical consistency. Unlike traditional compensation techniques, VLT enables effective coupling mitigation without requiring physical modifications to the array or continuous recalculations. We define two major antenna elements as current-driven (CD), such as a dipole antenna, and voltage-driven (VD), such as a patch antenna. In receiving arrays, we demonstrate that the open-circuit voltage, $V_{\text {oc}}$ , for CD elements and short-circuit current, $I_{\text {sc}}$ , for VD elements are inherently immune to mutual coupling. Simulation results show that the method successfully recovers embedded element patterns, closely matching isolated patterns even under severe coupling conditions. Experimental validation using a two-monopole prototype array with $0.13λ $ element spacing further confirms the effectiveness of VLT in eliminating mutual coupling effects in far-field radiation patterns.